Diet of the Mud-Flat Crab Helice tientsinensis in a Korean Salt Marsh - Bang, Jeong Hwan; Joo, Sungbae; Lee, Eun Ju; Kim, Min Seob; Jeong, Seonah; Park, Sangkyu (Wetlands, 2020)
Crabs live at high densities in intertidal zones with various halophytes in salt marshes. However, the ecological relationships between crabs and halophytes as well as the impacts of herbivorous crabs on the plant distribution are not fully understood. In this study, we identified halophytic plant species consumed by crabs and determined the relative contributions of halophytes and other food sources to the diet. A DNA analysis of stomach contents was used to determine plant food sources for crabs. We found that the dominant crab species Helice tientsinensis consumed Suaeda japonica, even though several halophytes inhabited the study site. These results indicated that H. tientsinensis is a selective feeder. Based on a stable isotope analysis, we observed a dietary shift during crab development. Immature individuals mainly ate soil organic matter, whereas mature individuals showed more diverse food sources. We observed greater plant (S. japonica) consumption by middle-sized crabs than by crabs of other sizes. Our results for the feeding relationship between crabs and plants extend our understanding of the benthic food web in salt marshes.
Keywords: Feeding habits; Food source; Helice tientsinensis; Korea; Siheung tidal flat; Suaeda japonica